P.087 The landscape of paediatric tuberous sclerosis complex (TSC) neurological care in canada: results from a national survey. (June 2022) - Nabavi Nouri, M; Zak, M; Whitney, R; Haile, D
Abstract : Background: Tuberous Sclerosis Complex (TSC) is a genetic disease that affects multiple body systems with the neurological manifestations causing the greatest disease burden. The objective of this study was to understand the scope of neurological TSC care delivery across Canada. Methods: A survey was developed after literature review and discussion amongst two Paediatric Epileptologists and one Nurse Practitioner with expertise in TSC. Canadian Paediatric Neurologists participated via an anonymous web-based survey through the Canadian League Against Epilepsy (CLAE) and Canadian Neurological Sciences Federation (CNSF). Results: Fifty-eight responses were received. A dedicated TSC clinic was reported by 24% (n=14). Sixty percent (n= 35) reported preforming serial screening EEG monitoring in infants and 58% (n= 34) started prophylactic therapy when EEG abnormalities occurred. Vigabatrin was used in 37% (n=21). For management of drug-resistant epilepsy, surgery was reported as the preferred therapeutic option in 57% (n=32) of respondents. Barriers to treatment identified were a lack of multi-disciplinary care, unfamiliarity with new therapies and insufficient resources. Conclusions: Our findings demonstrate the variability in neurological care delivery of patients with TSC. With few dedicated TSC clinics, there is a need for the establishment of a national network to support clinical practice, research and education.